Fairy tale images as a component of cultural programming: gender aspect: Сказочные образы как составляющая культурного программирования: гендерный аспект - Tomskaya, Maria (Przegląd Wschodnioeuropejski, 2020)
The paper considers male and female images in the Yakut fairy tales as a component of cultural programming of gender behavior in a tribal society. The analysis of the Yakut fairy tales reveals that the main male characters whole being integral are represented as a rule by three types – in the image of heroes, hunters and poor men. Female images are more diverse, among them there are girls of the Upper World and udagans (shaman women), endowed with magical powers and the gift of transformation; girls of the Middle World, who can be both passive and active characters; the third group of female images is represented by old women, who are often embodied in the collective image of the old woman Simekhsin. The results of the analysis suggest that the masculine images correspond to the stereotypical male behavior patterns in the patriarchate society, while the feminine images may deviate from the accepted gender stereotypes for various reasons.